When Is the Complement of the Comaximal Graph of a Commutative Ring Planar?. (6th April 2014) - Visweswaran, S.; Parejiya, Jaydeep
Abstract : Let R be a commutative ring with identity. In this paper we classify rings R such that the complement of comaximal graph of R is planar. We also consider the subgraph of the complement of comaximal graph of R induced on the set S of all nonunits of R with the property that each element of S is not in the Jacobson radical of R and classify rings R such that this subgraph is planar.